Real-world Efficacy of Direct-Acting Antiviral Therapy for HCV Infection Affecting People Who Inject Drugs Delivered in a Multidisciplinary Setting. (23rd May 2018) - Alimohammadi, Arshia; Holeksa, Julie; Thiam, Astou; Truong, David; Conway, Brian
Abstract: Background: Many clinicians and insurance providers are reluctant to embrace recent guidelines identifying people who inject drugs (PWID) as a priority population to receive hepatitis C virus (HCV) treatment. The aim of this study was to evaluate the efficacy of direct-acting antiviral (DAA) HCV therapy in a real-world population comprised predominantly of PWID. Methods: A retrospective analysis was performed on all HCV-infected patients who were treated at the Vancouver Infectious Diseases Centre between March 2014 and December 2017. All subjects were enrolled in a multidisciplinary model of care, addressing medical, psychological, social, and addiction-related needs. The primary outcome was achievement of sustained virologic response (undetectable HCV RNA) 12 or more weeks after completion of HCV therapy (SVR-12). Results: Overall, 291 individuals were enrolled and received interferon-free DAA HCV therapy. The mean age was 54 years, 88% were PWID, and 20% were HCV treatment experienced. At data lock, 62 individuals were still on treatment and 229 were eligible for evaluation of SVR by intent-to-treat (ITT) analysis. Overall, 207 individuals achieved SVR (90%), with 13 losses to follow-up, 7 relapses, and 2 premature treatment discontinuations. ITT SVR analysis show that active PWID and treatment-naïve patients were less likely to achieve SVR ( P = .0185 and .0317, respectively). Modified ITT analysis of active PWID showed no difference in achieving SVR ( P = .1157) compared with non-PWID. Conclusion: Within a multidisciplinary model of care, the treatment of HCV-infected PWID with all-oral DAA regimens is safe and highly effective. These data justify targeted efforts to enhance access to HCV treatment in this vulnerable and marginalized population.